2007
DOI: 10.1002/hep.21737
|View full text |Cite|
|
Sign up to set email alerts
|

Neutrophil dysfunction in alcoholic hepatitis superimposed on cirrhosis is reversible and predicts the outcome

Abstract: Mortality in patients with alcoholic hepatitis (AH) remains high, and although corticosteroids are widely used for treatment, the results vary considerably. In AH, neutrophils are primed and infiltrate the liver to produce injury, but paradoxically, the main cause of death in such patients is infection. Our prospective study addressed this paradox of primed neutrophils on the one hand and increased risk of infection on the other. We hypothesized that the full activation of neutrophils by a humoral factor such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
295
2
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 302 publications
(318 citation statements)
references
References 36 publications
12
295
2
9
Order By: Relevance
“…A few human diseases have been described to be associated with a Th17 phenotype, namely: multiple sclerosis, inflammatory bowel diseases, rheumatoid arthritis, Lyme disease, contact dermatitis, psoriasis, and uveitis. 19,23,39 Many different cell types, including T lymphocytes, monocytes, and neutrophils, which are primed in ALD, [40][41][42] might be responsible for the high IL-17 plasma levels observed in ALD. 22 The flow cytometry analysis showed that peripheral CD4 ϩ T lymphocytes from AC patients expressed much more IL-17 than those of HS, whereas no difference was seen for IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…A few human diseases have been described to be associated with a Th17 phenotype, namely: multiple sclerosis, inflammatory bowel diseases, rheumatoid arthritis, Lyme disease, contact dermatitis, psoriasis, and uveitis. 19,23,39 Many different cell types, including T lymphocytes, monocytes, and neutrophils, which are primed in ALD, [40][41][42] might be responsible for the high IL-17 plasma levels observed in ALD. 22 The flow cytometry analysis showed that peripheral CD4 ϩ T lymphocytes from AC patients expressed much more IL-17 than those of HS, whereas no difference was seen for IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of endotoxins and activation of Kupffer cells in the pathogenesis of ALC is evidenced by experimental studies in animals (8-10) and humans (10,11). Adachi et al (12,13) showed that Kupffer cell inactivation by gadolinium chloride, intestinal sterilization and targeted disruption of the genes encoding the LPS recognition receptor CD14 and the toll-like receptor 4 (TLR4) protected the animals from alcohol induced liver injury (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…steroids) are harder to assess. 2,8 Provocative associations between beta blocker use and impaired neutrophil function in a selected subset, and the putative interaction with elevated ammonia (and its implication) need to be explored further in larger studies. 5,9 …”
mentioning
confidence: 99%